Postoperative analgesic effect of hydromorphone in patients undergoing single-port video-assisted thoracoscopic surgery: a randomized controlled trial - Bai Y; Sun K; Xing X; Zhang F; Sun N; Gao Y; Zhu L; Yao J; Fan J; Yan M (Journal of Pain Research, 2019)
Yongyu Bai,1 Kai Sun,1 Xiufang Xing,1 Fengjiang Zhang,1 Na Sun,2 Yibo Gao,1 Ling Zhu,3 Jie Yao,3 Junqiang Fan,3 Min Yan11Department of Anesthesiology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310009, People’s Republic of China; 2Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou 221004, People’s Republic of China; 3Department of Thoracic Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310009, People’s Republic of ChinaObjective: To study the general efficacy of hydromorphone as a systemic analgesic in postoperative pain management following single-port video-assisted thoracoscopic surgery (VATS) and to explore the optimal administration regimen.Methods: A prospective, randomized, double-blind study was designed and conducted in a tertiary hospital. In total, 157 valid patients undergoing single-port VATS were randomly allocated into three groups. A total of 53 patients received morphine bolus only for postoperative analgesia (Group Mb); 51 patients received a hydromorphone background infusion plus bolus (Group Hb + i), and 53 patients received a hydromorphone bolus only (Group Hb). The primary outcomes were patient-reported static and dynamic pain levels; the secondary outcomes included side effects, sleep quality, and recovery indexes.Results: Patients in Group Hb + i experienced lower pain intensity (approximately 10 out of 100 on the visual analog scale) in both static pain and dynamic pain in the days following surgery (P<0.01), better sleep quality during the first night only (P=0.002), and a higher satisfaction level than those in the other two groups (P=0.006). A comparison of these variables in Group Mb and Group Hb resulted in no significant differences. Lastly, side effects and recovery indexes remained the same among bolus-only groups and bolus-plus-background-infusion groups.Conclusion: There is no advantage to administering hydromorphone over morphine using bolus only mode. Within 24 h after surgery, a background infusion should be considered as a part of a standard protocol for patient-controlled intravenous analgesia. At 24 h after surgery, the background infusion should be adjusted in accordance with patient preferences and pain intensity.Keywords: morphine, background infusion, sleep quality, patient satisfaction